The Level Of Perception Of Students Towards Fi Sabilillah Zakat Distribution: Case Study Of Universiti Sains Islam Malaysia - Muhamad Firdaus Ab Rahman; Hussein 'Azeemi Abdullah Thaidi; Azman Ab. Rahman; Nor Hafizah Mohd Aziad; Mohd Hafiz Safiai; Mohammad Naqib Hamdan (Morse Florse, 2024)
Islam In Malaysia, management-related zakat issues differ between each state. Besides, most higher education institutions in Malaysia have a specific unit or department which handles the collection and distribution of zakat in their institutions. However, the distribution of zakat to fīsabīlillahbeneficiary (aṣnāf), students' comprehension and trust remain uncertain. This study evaluates the level of awareness among students related to the Awqaf and Zakat Center (PWZ) and their perception of zakat distribution to fīsabīlillahaṣnāf in UniversitiSains Islam Malaysia.This research uses a quantitative approach to collect data via the questionnaire. One hundred (100) students from UniversitiSains Islam Malaysia are among the samples. The result shows that while respondents have a good understanding of zakat management mean at (3.91), adequate information has not been obtained from certain management elements such as customer relations mean at (1.30) and advertising mean at (0.80). Besides, the zakat distribution criterion remains uncertain mean at (1.36). The finding shows that most respondents lack faith in the distribution of zakat from PWZ while being aware of the work of PWZ. Therefore, PWZ should play an essential role in supporting financially burdened students.